2021
DOI: 10.1136/bmjopen-2020-046745
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on rural communities: a cross-sectional study in the Sichuan Province of China

Abstract: ObjectiveRecently, China has experienced a considerable influence of the COVID-19 pandemic on the local people’s health and economy. Hence, the current research aims to investigate the psychological and socioeconomic impact of COVID-19 on rural communities in the Sichuan Province of China.MethodsA total of 499 participants (village representatives of Sichuan Province) were approached to partake in a cross-sectional online survey and share their experience regarding the ongoing pandemic. The descriptive statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
8
0
2
Order By: Relevance
“…These practices may vary according to rurality [ 12 ], due to the fact that in rural areas, there is less purchasing power and less access to health and social services [ 13 , 14 ]. In addition, in rural areas, sociocultural factors, greater informal commercial activity and larger households could modify compliance with preventive measures compared to urban areas [ 9 ], since these characteristics could condition a greater need to obtain economic income during restrictive measures [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These practices may vary according to rurality [ 12 ], due to the fact that in rural areas, there is less purchasing power and less access to health and social services [ 13 , 14 ]. In addition, in rural areas, sociocultural factors, greater informal commercial activity and larger households could modify compliance with preventive measures compared to urban areas [ 9 ], since these characteristics could condition a greater need to obtain economic income during restrictive measures [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This review found that six articles (Bossenbroek & Ftouhi, 2021;Cevher et al, 2021;Fang et al, 2021;Landry et al, 2021;Quandt et al, 2021;Shafi et al, 2021) described the effect of pandemic on mental health in farmers such as anxiety, fear, worry, depression, stress and substance use disorders. Psychological problems during COVID-19 can be directed by the impact of the disease, restriction that lead to limited access to social support facilities and uncertainty and stress resulting from loss jobs and livelihoods (Semo & Frissa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The review found that farmers face a mental health problems such as anxiety (Bossenbroek & Ftouhi, 2021;Cevher et al, 2021;Fang et al, 2021), Fear, worry (Quandt et al, 2021), depression (Fang et al, 2021) stress (Shafi et al, 2021), substance use disorders (Landry et al, 2021).…”
Section: Impact Of Covid-19 To Mental Health Farmersmentioning
confidence: 99%
“…A pesar de ello, el tipo de áreas de residencia no parecen considerarse un elemento que regule la afectación de la COVID-19 en la salud mental de la población, al igual que otras características como el número de personas convivientes (Pinedo et al, 2021). En este caso, más de la mitad de la muestra proviene de áreas rurales, lo que indica que también ha existido un impacto en la salud mental de la población de estas áreas durante el periodo de tiempo de la pandemia, resultando coincidente con un estudio realizado en Sichuan (China) (Shafi et al, 2021), en el que no existe una tendencia de la población rural a considerar la pandemia causante directa de su malestar emocional.…”
Section: Discussionunclassified